An integral formula for the coefficients of the inverse cyclotomic polynomial - Andrica Dorin; Bagdasar Ovidiu; Ţurcaş George Cătălin (Analele Stiintifice ale Universitatii Ovidius Constanta: Seria Matematica)
Some recent advances related to an integral formula for the coefficients of inverse cyclotomic polynomials, including applications and numerical simulations are given.